Hubungan Kolesterol Total dengan Hipertensi Pada Pegawai PTM Kementrian PANRB Tahun 2024 - Luberiyatun, Nurrohmah; Barkah, Asep (Universitas Malahayati, 2025)
ABSTRACT Background: The relationship between hypertension and lipid abnormalities, especially total cholesterol levels, has been proven. The presence of dyslipidemia increases the risk of developing hypertension. Cholesterol is a modifiable risk factor in relation to hypertension. The higher the total cholesterol level, the greater the chance of developing hypertension. Purpose of writing: To determine the relationship between total cholesterol and hypertension in PTM employees of the Ministry of PANRB. Research Method: This type of quantitative research uses a descriptive design, cross sectional study approach, the sample in this study was 69 people, chi square analysis test. Research Results: There is a relationship between total cholesterol and hypertension, p value = 0.048. Conclusions and Recommendations: The results of this research are expected to provide in-depth insight into the relationship between total cholesterol levels and hypertension, as well as provide a basis for appropriate preventive measures to maintain the health of Ministry of PANRB employees. Keywords: Hypertension, Total Cholesterol, Employee ABSTRAK Hubungan antara hipertensi dan abnormalitas lipid, khususnya kadar kolesterol total, telah terbukti. Kehadiran dislipidemia meningkatkan risiko terjadinya hipertensi. Kolesterol merupakan faktor risiko yang dapat diubah dalam hubungannya dengan hipertensi. semakin tinggi kadar kolesterol total, semakin besar kemungkinan terkena hipertensi. Untuk mengetahui hubungan kolesterol total dengan hipertensi pada pegawai PTM Kementrian PANRB. Jenis penelitian kuantitatif dengan menggunakan desain deskriptif pendekatan cross sectional study, sampel pada penelitian ini berjumlah 69 orang, uji analisis chi square. Terdapat hubungan kolesterol total dengan hipertensi nilai p value=0.048. Hasil penelitian ini diharapkan dapat memberikan wawasan mendalam tentang hubungan antara kadar kolesterol total dan hipertensi, serta memberikan dasar untuk langkah-langkah preventif yang tepat untuk menjaga kesehatan pegawai Kementerian PANRB. Kata Kunci: Hipertensi, Kolesterol Total, Pegawai